Prevention of aspirin-induced faecal blood loss by prostaglandin E2. Issue 7 (July 1980) - Cohen, M M; Cheung, G; Lyster, D M
Abstract : Prostaglandins have been shown in animal laboratory studies to be capable of protecting the gastrointestinal tract against injury by exogenous agents. This study was conducted to determine if prostaglandin E2 (PGE2), which is native to the human gastric mucosa, could influence the increase in faecal blood loss associated with the ingestion of aspirin (ASA). A randomised double-blind study was performed on 27 healthy men. Faecal blood loss was measured by the 51Cr labelled red cell technique. ASA (600 mg four times daily) caused a significant increase in faecal blood loss. PGE2 (1 mg four times daily) had no effect on faecal blood loss when administered alone. When given in addition to ASA it resulted in a faecal blood loss not significantly different from control. No significant alteration in intestinal transit occurred. It is concluded that PGE2 protects man from the gastrointestinal injury associated with ASA.